CHALLENGES OF TRANSLATION - Egamberdiyeva Iroda Abdurahimovna; Toshtemirova Nilufarkhon Ashurali kizi (TADQIQOTLAR, 2025)
Abstract: Translation, a fundamental act of cross-cultural communication, involves transferring meaning from one language into another while preserving linguistic, cultural, and contextual nuances. Despite technological advancements, translators still face multifaceted challenges ranging from linguistic differences to cultural disparities and domain-specific complexities. This article explores the principal challenges encountered in translation, including lexical gaps, idiomatic expressions, syntactic variations, cultural references, and technical language. Additionally, it discusses the impact of machine translation and the importance of human intuition in the process. The study emphasizes the need for skilled translators with interdisciplinary knowledge and cultural sensitivity to ensure effective communication across languages.